ELASTO-PLASTIC BEHAVIOR OF THERMOPLASTIC MATRIX ROLLER CHAIN LINK PLATES REINFORCED WITH STEEL FIBERS - Arslan, Nurettin; Sancaktar, Erol; Celik, Mehmet (American Society of Mechanical Engineers (ASME), 2000)
The elastic and elasto-plastic stress analysis of thermoplastic matrix roller chain link plates reinforced with steel fibers is performed by using Finite Elements Analysis (FEA). A two-dimensional finite element computer program is developed for elasto-plastic stress analysis. Isoparametric quadratic element with four nodes is used with Lagrange polynomial as an interpolation function. The results of elastic and elasto-plastic finite element stress analysis by using the computer program prepared, are compared with experimental, (photoelastic) results. The spreads of the plastic zones due to the external load applied on the pin-hole of the plate and variations of the residual stresses are determined in different orientation angles and loads. It is shown that the geometry of the link plates can be designed to decrease the stress concentrations. Furthermore, it is shown that the tensile load limit of the roller chain link plate is extended by the residual stresses. Copyright © 2000 by ASME.
ASME 2000 International Design Engineering Technical Conferences and Computers and Information in Engineering Conference, IDETC-CIE 2000 -- 10 September 2000 through 13 September 2000 -- Baltimore -- 186543
Keywords: Chains; Elastoplasticity; Finite element method; Reinforced plastics; Residual stresses; Steel fibers; Chain links; Elastic-plastic stress; Elasto-plastic behaviours; Elasto-plastic stress; Finite element analyse; Plate reinforced; Roller chains; Stresses analysis; Thermoplastic matrix; Two-dimensional; Stress analysis